Causal Associations Between the Gut Microbiota and Hypertension‐Related Traits Through Mendelian Randomization: A Cross‐Sectional Cohort Study - Yunfan Tian; Mingxia Gu; Dazhong Chen; Quanbin Dong; Yifeng Wang; Wei Sun; Xiangqing Kong (The Journal of Clinical Hypertension)
ABSTRACT Previous studies have suggested a link between the gut microbiome and hypertension‐related traits like blood pressure. However, these reports are often limited by weak causal evidence. This study investigates the potential causal association between gut microbiota and hypertension‐related traits using Mendelian randomization with summary data from genome‐wide association studies. The inverse‐variance weighted method revealed that the Clostridium innocuum group (Odds ratio [OR]: 1.0047, 95% confidence interval [CI]: 1.0004–1.0090, p = 0.0336), Eubacterium fissicatena group (OR: 1.0047, 95% CI: 1.0005–1.0088, p = 0.0266), Lachnospiraceae FCS020 group (OR: 1.0063, 95% CI: 1.0004–1.0122, p = 0.0361), and Olsenella (OR: 1.0044, 95% CI: 1.0001–1.0088, p = 0.0430) were associated with an increased risk of hypertension. Conversely, Flavonifractor (OR: 0.9901, 95% CI: 0.9821–0.9982, p = 0.0166), Parabacteroides (OR: 0.9874, 95% CI: 0.9776–0.9972, p = 0.0121), and Senegalimassilia (OR: 0.9907, 95% CI: 0.9842–0.9974, p = 0.0063) were associated with a decreased risk of hypertension. External validation with the Guangdong Gut Microbiome Project confirmed a negative correlation between Parabacteroides and hypertension, potentially through metabolic pathways. These findings provide further evidence supporting the hypothesis that microbes and their metabolites play a role in blood pressure regulation.